Why Is the World Getting Older? The Influence of Happiness on Mortality - Cahit Guven; Rudolph Saloumidis (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
World life expectancy has risen by around 20 years in the last 50 years. This period has also witnessed rising happiness levels around the world suggesting that happiness might be one of the causes behind the decline in mortality. We investigate the relationship between happiness and mortality using the German Socio-Economic Panel. We consider doctor visits, self-reported health, and presence of chronic illness as health measures. After controlling for initial health conditions, we find that happiness extends life expectancy. 10 percent increase in happiness decreases probability of death by four percent, and this effect is more pronounced for men and younger people. Happiness plays a more important role for chronically ill people in decreasing mortality than for those who are not chronically ill. The positive influence of happiness on mortality can offset the negative impact of chronic illness. Marriage decreases mortality and this effect appears to work through increased happiness.
Keywords: D3; I10; I12; 330; Happiness; mortality; health; chronic illness